Nitric oxide inhibits the ATPase activity of the chaperone-like AAA + ATPase CDC48, a target for S-nitrosylation in cryptogein signalling in tobacco cells - Astier, J.; Besson-Bard, A.; Lamotte, O.; Bertoldo, J.; Bourque, S.; Terenzi, H.; Wendehenne, D.
NO has important physiological functions in plants, including the adaptative response to pathogen attack. We previously demonstrated that cryptogein, an elicitor of defence reaction produced by the oomycete Phytophthora cryptogea, triggers NO synthesis in tobacco. To decipher the role of NO in tobacco cells elicited by cryptogein, in the present study we performed a proteomic approach in order to identify proteins undergoing S-nitrosylation.We provided evidence that cryptogein induced the S-nitrosylation of several proteins and identified 11 candidates, including CDC48 (cell division cycle 48), a member of the AAA+ ATPase (ATPase associated with various cellular activities)family. In vitro, NtCDC48 (Nicotiana tabacum CDC48)was shown to be poly-S-nitrosylated by NO donors and we could identify Cys 110, Cys526 and Cys664 as a targets for S-nitrosylation. Cys526 is located in the Walker A motif of the D2 domain, that is involved in ATP binding and was previously reported to be regulated by oxidative modification in Drosophila. We investigated the consequence of NtCDC48 S-nitrosylation and found that NO abolished NtCDC48 ATPase activity and induced slight conformation changes in the vicinity of Cys526. Similarly, substitution of Cys526 by an alanine residue had an impact on NtCDC48 activity. More generally, the present study identified CDC48 as a new candidate for S-nitrosylation in plants facing biotic stress and further supports the importance of Cys526 in the regulation of CDC48 by oxidative/nitrosative agents.
Keywords: CELL DIVISION CYCLE 48 (CDC48); CRYPTOGEIN; NITRIC OXIDE (NO); PLANT DEFENCE RESPONSES; S-NITROSYLATION